The Influence of Leadership and Work Discipline on Teacher’s Job Satisfaction - Rahmawati, Suci; Fitria, Happy; Putra, Alhadi Yan (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to provide a description of the impact of leadership and work discipline on teacher’s job satisfaction at SMA PGRI 2 Palembang. A quantitative technique was used in the research. According to the findings of the study, partial leadership has a favorable and substantial impact on teacher work satisfaction at SMA PGRI 2 Palembang. Similarly, it is suggested that there is a favorable and significant impact of partial assessment of work discipline on teacher’s job satisfaction. The examination of leadership and work discipline at the same time has a good and significant influence on teacher’s job satisfaction.